FIRST CLASS AT LAST! : London-Bangkok-Singapore.... the ultimate travel experience. - 234260 Forsyth, Patrick (London, : Marshall Cavendish Editions, 2007)
Fed up with the strenuous process of travel: the slow queues, the delays, the crowds and the extreme discomfort of the average economy airline seat? This work presents an account of luxury travel and highlights what every traveller secretly longs to do - travel in style and grandeur.